Implementation of Touchless Automatic Hand Washer in Community Service Towards Adaptation of New Habits in Covid-19 Pandemic in Bandung City - Dina Angela; Tunggul A. Nugroho; Yoyok Gamaliel (Journal of Innovation and Community Engagement, 2023)
Available handwashing sinks, especially during the early days of the Covid-19 pandemic, still required users to directly touch the water faucet and soap bottles. There were no guidelines for correct hand washing according to World Health Organization (WHO) standards, and water was simply wasted because the faucet was left open while scrubbing hand. Therefore, a device was developed in the form of a touchless hand-washing faucet using a sensor that can detect the presence of hands when one performing hand washing so that water only flows out when needed. The device is also equipped with a soap measuring system and indicators for soap or water containers that are full, half, or empty. To ensure that users can wash their hands properly, the device is also equipped with an announcer containing instructions for washing hands according to WHO standards. The developed device has been implemented in the field by installing it in three public places in the city of Bandung. The public can directly use this devices to fight the Covid-19 outbreak.